The Difference of Anxiety between Primigravida and Multigravida Patients in Third Trimester Pregnancy at Permata Bunda Hospital Purwodadi - Himawan, Ichsanul Amy; Suwito, Djoko; Hartanto, Rifai (Nexus Kedokteran Klinik, 2012)
Background: Anxiety can be experienced by humans, characterized by the fear, unpleasant, and often accompanied by autonomic symptoms. Pregnant woman may experience anxiety, especially in the third trimester, and there may be differences in anxiety in primigravida and multigravida. This study aims to determine the difference of anxiety level between primigravida and multigravida patient in the third trimester of pregnancy. Methods: The research was descriptive analytic study with cross sectional approach was conducted to patients in obstetry and gynecology clinic Permata Bunda Hospital Purwodadi on March 2012. Sixty samples were choosen by random purposive sampling. The samples were (1) thirty primigravida patients and thirty multigravida patients, (2) third trimester pregnancy. Samples were excluded if (1) LMMPI score more than 10, (2) Family death and suddenly incident like accident in last 3 month, (3) severe physical illness. This research was analized by Mann Whitney test by Statistical Product and Service Solution (SPSS) Program 17.00 for Windows. Results: Average score of primigravida 20,1000 Â± 1,30811, and multigravida 24,2000 Â± 1,02318. The result of Mann-Whitney test was p = 0,015. ( p < 0,05) Conclusions: This research found a significant difference of anxiety level between primigravida and multigravida patients in third trimester pregnancy at Permata Bunda Hospital Purwodadi. Keywords: anxiety, pregnancy, primigravida, multigravida, third trimester.Â